Children's encyclopedia: space - Miles, Kelly (Essex: Miles Kelly, Thaxted, 2015)
This beautifully illustrated encyclopedia is the perfect book to encourage a child's interest in space. Children's Encyclopedia Space covers a wide variety of subjects, including the Big Bang, star life cycles, space telescopes and astronauts. Easy-to-follow numbered facts give children a great sense of achievement and incentivise them to make their way through the book. Colourful photos, artwork and diagrams aid the learning process, alongside quizzes, activities and cartoons to make learning fun and accessible
Keywords: Space